Etyczne doktryny Kościoła i ich sprzeniewierzenie w mediach - Grochowski, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Every man has to make moral (ethical) decisions, whether they are quite insignificant or are those discussed on the front pages of newspapers and on TV screens. One may refer to Plato here, who said millennia ago that instead of admiring wise philosophers people concentrate their attention on silver-tongued politicians and the promises they make. Ethics and morality can be treated as inextricable. Whereas morality concerns the realm of decisions and acts, however, ethics concerns our considerations of these acts. Truth is the most significant element related to the ethical and moral consideration of the media and the Church. In August 1993 Pope John Paul II published an encyclical letter Veritatis Splendor (The Splendor of Truth), where he presented ethical matters concerning truth. In the world of the media it is not always obvious what is meant by somebody speaking about truth. Arealistic expression of truth is provided by what is in agreement with the status quo that is independent from this truth. In this approach there is only one truth and it is decided by factual truth or falsity. This is the point of view the Church recognizes.